(untitled) (Actual Problems of Mind, 2021)
This article is the Ukrainian translation of Chapter 6 “Of Mr. Locke’s Account of Our Personal Identity” from T. Reid’s “Essays on the Intellectual Powers of Man”. In this chapter, T. Reid gives definitions to main terms: “personal identity” and “person” and puts forward a number of critical remarks concerning the Lockean concept of personal identity. T. Reid defines identity as a continued existence of an intelligent being over time. He considers identity as an integral feature of personhood: there is no person, who wouldn’t be identical over time. Critical remarks concern the content of J. Locke’s concept, and they also have methodological nature. T. Reid opposes J. Locke’s attempt to develop the concept of personal identity, which was based on consciousness as a criterion of identity. According to T. Reid, the continuity of the self over time cannot be explained by the existence of consciousness, because consciousness, or self-awareness of a person, does not have the same fundamental ontological status as substance. The identity between the two stages in a person’s existence over time is easy to violate, because the transitivity between the stages is lost due to forgetfulness. T. Reid argues that consciousness is replaced by memory in Locke’s concept. Consciousness is by nature flowing and transient. It changes every moment, so it cannot be the basis of identity. T. Reid emphasizes that “personal” denotes an individual, while in Locke’s concept it begins to be used as a sortal term. The very fact of the existence of consciousness does not explain how a person keeps personal identity overtime, because in this case all people were identical to each other. Methodological remarks on the Lockean concept relate to the inconsistency of the use of concepts that lead to contradictions between the main theses and Locke’s attempt to call the criterion of identity what is really a consequence of identity: to be conscious, a person must remain personal identity. In this chapter, T. Reid considers a though-experiment about a boy, an officer and a general, which has become a classic among though-experiments on the problem of personal identity. In this experiment, the philosopher argues that consciousness is an unreliable criterion of personal identity because it is easy to violate. As a result, one and the same individual ceases to be identical to themselves at different stages of their life, therefore ceases to be the same person.